2021
DOI: 10.1002/adma.202008084
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Lithium Metal Batteries with Extended Cycling Enabled by Dynamic Adaptive Solid‐State Interfaces

Abstract: Improving the long-term cycling stability of solid-state lithium (Li)-metal batteries (SSBs) is a severe challenge because of the notorious solid-solid interfacial contact loss originating from the repeated expansion and contraction of the Li anodes. Here, it is reported that high-performance SSBs are enabled by constructing brick-and-mortar electrolytes that can dynamically adapt to the interface changes during cycling. An electrolyte film with a high mechanical strain (250%) is fabricated by filling viscoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 49 publications
0
67
0
Order By: Relevance
“…While the PEO/PEG electrolyte without LGPS fillers exhibited much lower conductivity of only 1.54 × 10 −4 S cm −1 at room temperature. The polarization of the symmetric battery with LGPS-PEO/PEG was no more than 80 mV after operating for 6700 h. Liu et al [19] prepared the electrolyte by filling viscoelastic and piezoelectric block-copolymer electrolytes into a mixed conductor Li 0.33 La 0.56 TiO 3-x nanofiber film (PPLL). Li 0.33 La 0.56 TiO 3-x was demonstrated to react with lithium when in contact, generating a hybrid ionic/electron conductive interface (electron conductivity = 0.02 S m −1 ) and minimizing the inhomogeneity of the electric field on the surface of lithium anode.…”
Section: Solid Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…While the PEO/PEG electrolyte without LGPS fillers exhibited much lower conductivity of only 1.54 × 10 −4 S cm −1 at room temperature. The polarization of the symmetric battery with LGPS-PEO/PEG was no more than 80 mV after operating for 6700 h. Liu et al [19] prepared the electrolyte by filling viscoelastic and piezoelectric block-copolymer electrolytes into a mixed conductor Li 0.33 La 0.56 TiO 3-x nanofiber film (PPLL). Li 0.33 La 0.56 TiO 3-x was demonstrated to react with lithium when in contact, generating a hybrid ionic/electron conductive interface (electron conductivity = 0.02 S m −1 ) and minimizing the inhomogeneity of the electric field on the surface of lithium anode.…”
Section: Solid Electrolytementioning
confidence: 99%
“…[ 18 ] The design of the organic/inorganic hybrid solid electrolyte and the electrolyte/electrode interface layer improve the contact between the solid electrolyte and the lithium anode. [ 19 , 20 ] A variety of methods guiding Li + (such as, lithiophilic sites, gradient electrical conductivity, reconstructed lattice plane) contribute to the uniform and compact deposition of lithium in the 3D host. [ 21 , 22 , 23 ] Compared with the concentrated mono‐salt, the concentrated dual‐salt effectively improves the ion conductivity of the high‐concentration electrolyte (HCE) system.…”
Section: Introductionmentioning
confidence: 99%
“…LLTO reacts readily with lithium metal and changes color from white (pristine) to deep black due to the ease of reduction of Ti 4+ cation to lower oxidation state Ti 3+ specie as evidenced by X-ray photoelectron spectroscopy (XPS) studies [82]. This also accompanied with the formation of oxygen vacancies which in turn makes the interface very conductive electronically and not suitable as an electrolyte for lithium metal battery [82]. Liu et al [82] confirmed that black LLTO showed two new peaks at the lower binding energies corresponding to the formation of Ti 3+ with lower electron densities.…”
Section: Ti Reduction At the Interfacementioning
confidence: 99%
“…To solve above‐mentioned issue, an integrated flexible solid‐state lithium battery with a self‐compatible interface is constructed by Liu et al., which is a smart solid‐state battery with enhanced interface compatibility and dynamic adaptability. The interface can dynamically accommodate the change of the solid‐solid interface during the long cycle due to its highly viscoelastic and piezoelectrical (Figure 6b) [103] …”
Section: Modifications At Electrolyte/electrode Interfacementioning
confidence: 99%